Análise experimental da velocidade de ascensão de uma bolha de gás escoando em líquido estagnado: influência da inclinação do tubo - Baldykowski, Bruno (2023)
Multiphase flow, characterized as having more than one phase (gas, liquid, or solid), is present in various natural systems and diverse industrial applications. In the petroleum industry, for example, it occurs during the production and transportation of oil and gás through horizontal, vertical, or inclined pipes. Due to the exponential need for optimization in the industrial field, determining the parameters that govern these phenomena becomes essential. Thus, simplifying the multiphase flow to the two-phase system facilitates understanding and calculation, enabling the study of this complex physical phenomenon. However, intermittent flow stands out among the various flow patterns due to its complexity and extensive application in pipelines of different slopes. In this context, an adaptation was designed in an experimental gas-liquid flow apparatus, and experimental tests were conducted at different slopes to obtain the elongated bubble velocity, which was subsequently compared with literature results. Using the apparatus and developed methodology, the velocity was determined from videos recorded by a digital camera that captured the bubble’s passage through two predetermined points. Through video post-processing programs, the velocity was obtained by considering the time and distance traveled by the bubble. A set of measurements for slopes ranging from 0° to 90°, at intervals of 15°, was analyzed, obtaining the average values of Froude number (0.395; 0.462; 0.493; 0.485; 0.449; 0.396; 0.350) and the relative deviations from the results in the literature (GÓMEZ-BUENO, 2010) (1.33%; 1.32%; 0.42%; 1.23%; 2.07%; 0.77%; 5.58%). It is concluded, comparing the results obtained, that the values are in line with the others available in the literature and, thus, validating the data for applications in future research.